Geospatial Epidemiology of chicken-pox disease in India between 2015-2021: A GIS based analysis - Minhas, Akshay; Singh, Mitasha; Prasad, Nerella Satya Narayana; Bhardwaj, Ashok (Indian Journal of Community Health, 2022)
Introduction: In this paper, we introduce geographical information systems (GIS) as a tool to study trends in disease spread in time and space. Based on data gathered by the integrated disease surveillance programme (IDSP), we can see where outbreaks of Chickenpox have occurred. Objective: The aim of this study is to assess the trends in chickenpox diseases in India between January 2015 and April 2021 using GIS maps. Methods: For the collection of secondary data relating to chickenpox, a free app called collect 5 was used for collecting data weekly from the IDSP website and then storing them in an online server. In this project, variables that needed to be processed with QGIS were combined with table attributes of many shapefiles of India and presented as maps. Results: Between Jan 2015 and May 2021, 1269 chickenpox outbreaks (27,257 cases) have been recorded. Thirty-one deaths have been confirmed, with most occurring in Bihar and Uttar Pradesh. Nineteen states did not report any deaths. According to the seasonally adjusted trend, the number of cases was highest during the months of January and March. Conclusion: In summary, geographic information systems have become an invaluable tool for mapping the hotspots of acute epidemics and planning public health interventions to prevent the spread of these diseases.